Association rules between the microstructure and physical mechanical properties of rock-mass under coupled effect of freeze-thaw cycles and large temperature difference - Jiang, Haibo; Mo, Zuguo; Hou, Xiongbin; Wang, Haijuan (Penerbit Universiti Kebangsaan Malaysia, 2017)
The mechanical properties of fractured rock mass are largely dependent on the fracture structure under the coupling of freeze-thaw cycles and large temperature difference. Based on the traditional macroscopic continuum theory, the thermal and mechanical model and the corresponding theories ignore the material internal structure characteristics, which add difficulty in describing the mesoscopic thermal and mechanical behavior of the fractured rock mass among different phases. In order to uncover the inherent relationship and laws among the internal crack development, structural change and the physical and mechanical properties of rock under strong cold and frost weathering in cold area, typical granite and sandstone in cold region were analyzed in laboratory tests. The SEM scanning technology was introduced to record the microstructural change of rock samples subject to freeze-thaw cycles and large temperature difference. Association rules between the microstructure and the physical mechanical properties of rock mass were analyzed. The results indicated that, with the increase of the cyclic number, the macroscopic physical and mechanical indexes and the microscopic fracture index of granite and sandstone continuously and gradually deteriorate. The width of original micro crack continues to expand and extend and new local micro cracks are generated and continue to expand. The fracture area and width of the rock increase and the strength of the rock is continuously damaged. In particular, the strength and elastic modulus of granite decrease by 20.2% and 33.36%, respectively; the strength and elastic modulus of sandstone decrease by 33.4% and 36.43%, respectively.